Surgical outcome of extra sinus zygomatic implants in comparison to conventional implants for the rehabilitation of atrophic maxilla: a systematic review and meta-analysis - Patel, Ruchi S.; Metgud, Renuka M. (International Journal Of Community Medicine And Public Health, 2024)
Posterior maxillary atrophy in particular presents a challenge for implant-supported dental rehabilitation. The discovery of the zygomatic implant by Branemark and its modifications has brought a much-needed window of hope to most patients with atrophic maxilla. The conventional approach to is believed to be the intra sinus technique but the use of the extra sinus zygomatic implants has advantages like reducing surgical time, the risk of sinus adverse events and improving surgical visualization. A systematic literature search in five databases: Proquest, Google Scholar, PubMed, OVID, Cochrane and a hand search of relevant scientific journals was performed. The meta-analysis done on the included five studies, revealed that the primary outcome, i.e, implant survival rate and prosthesis failure showed no statistically significant difference between the test and the control group. The overall difference between the control (intra sinus zygomatic implants) and test group (extra sinus zygomatic implant) was statistically significant for chronic sinusitis (p=0.0002) and periimplantitis (p=0.01). The use of the extra sinus technique for the placement of zygomatic implants simplified the surgical procedure, improved the prosthetic outcome and reduced the risk of sinusitis and periimplantitis as compared to conventional or intra sinus technique of zygomatic implant placement.